The Effectiveness Analysis of Computational Thinking Patterns and Levels of Students’ Meta-Cognitive Awareness in Solving Learning Problems - Sudadi Sudadi; Enos Lolang; Joko Ariawan; Iwan Henri Kusnadi; Misbahul Munir (Journal on Education, 2023)
The goal of this study is to characterize students' computational thinking skills in problem-solving in terms of their degree of metacognition awareness. The study is descriptive and qualitative in nature. The participants were selected using purposive sampling, comprising of two students with reflective metacognitive awareness, two students with strategic metacognitive awareness, two students with aware metacognitive awareness, and two students with tacit metacognitive awareness. The data was collected through written tests and interviews and analyzed based on the computational thinking indicators. The findings reveal that the computational thinking abilities of students who use metacognitive awareness in problem-solving are abstraction, pattern recognition, and decomposition. Furthermore, students with strategic metacognitive awareness exhibit proficiency in abstraction and pattern recognition. Additionally, students who use metacognition awareness through abstraction or decomposition exhibit computational thinking abilities when solving problems. However, students with tacit metacognitive awareness do not meet the computational thinking indicators while solving problems.